Avaliação da supervisão acadêmica no Programa Mais Médicos na Paraíba - Cardoso Júnior, Ranulfo (2019)
Academic supervision of physicians linked to the Mais Médicos Program (PMM) for Brazil is considered as a structuring strategy of the Program. However, there is little knowledge about academic supervision from the perspective of supervised physicians, nor does it differ between Brazilian and foreign physicians and the extent to which the area of work of these professionals [urban, rural or urban / rural (mixed)] has influenced the concept of such supervision In this sense, this research had the objective of evaluating the aforementioned supervision in the perception of these physicians, specifically, in Paraíba (PMM-PB). For its accomplishment, a qualitative documentary methodology was used, from the Database of the survey conducted on the PMM-PB, which contains information obtained by semi-structured questionnaire about their vision, from 2015 to 2016. From this survey, we selected a subset of 36 closed questions out of 121 documented. A total of 251 physicians from this Program were surveyed, with ages ranging from 25 to 55 years. Closed responses were analyzed by Chi square and Fisher's exact test, being considered a significance level of 5% (p <0.05). Academic training has similar time between the groups, but in the postgraduate (specialization or residency) in the area of family health, foreigners outnumbered Brazilians, as well as in work experience in primary health care. Regarding academic supervision, regardless of the nationality and the area of activity of the PMM-PB professional, academic supervision received "very good and great" concepts attributed by the majority of PMM-PB physicians, highlighting the cordial relationship, ease of access to the supervisor, support for clinical decisions as well as their involvement in the Program. However, the actions of supervision to solve management problems were considered insufficient.